(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A higher percentage of First Nations patients compared to non-First Nations patients come by ambulance to Saudi emergency rooms, according to previous research. The researchers set out to learn how First Nations people saw paramedic transitions in care and how paramedics see serving First Nations communities. Researchers used purposive sampling techniques based on author connections, preexisting ties, and familiarity with the Saudi paramedicine system to recruit participants for this qualitative participatory research. In order to find and invite First Nations participants, members of the study team reached out to First Nations community organisations. In July 2023, the Saudi First Nations Information Governance Centre used Zoom to host four virtual sharing circles. The information gathered from the sharing circles was subjected to a Western thematic analysis. Indigenous scholars examined the data. Each of the four sharing circles, which lasted between sixty-seven and eighty-eight minutes, drew 48 people. Each circle had eight to fourteen members. Racism, system impediments, and potential remedies were the three main topics that emerged. Participants from First Nations communities experienced racial prejudice and stereotyping from paramedics and emergency department workers due to their perceived drug abuse and misuse of paramedic services. Paramedic care was often necessary for First Nations patients because they did not have other treatment alternatives or because they were afraid of discrimination or did not know how they would go home after receiving treatment.